Healthy and Sustainable Territories: health care strategies for rural black population in Caruaru/Pernambuco - Thaís Cecília dos Santos Brito; Bianca Cardoso Peixinho; Juliana Camargo de Faria Pirró; Rosane Suellen de Oliveira; Polyana Loureiro Ferreira de Carvalho; Diogivânia Maria da Silva; Mariana Olívia Santana dos Santos (Centro Brasileiro de Estudos de Saúde, 2021)
ABSTRACT The socio-historical process in Brazil is crossed by racism and the agrarian issues, as both are part of the same structural dimension. Thus, the understanding of racism is essential to apprehend the social determination process of racial inequalities in health. This action research had as general objective to analyze the interference of racism in the health-disease-care process of rural black families and, more specifically, to describe the children's group intervention activities. Primary data were used: field diaries and other documents prepared by the Resident Team; and secondary data: the Participatory Rural Appraisal as a tool of systematization in territorialization. This shared action between professionals residents in Family Health Care and settlement dwellers, located in Caruaru (PE), was developed from the popular health education focusing on health promotion and facing racism as a transversal axis. In this sense, the Family Health team is a powerful tool for promoting Healthy and Sustainable Territories by confronting racism in its non-biocentered issues, with the use of low technology, transdisciplinary, strengthening black identities and building health as recommended in health policies and the Sustainable Development Goals.